THIRD LANGUAGE TRANSLATION STRATEGIES IN SUBTITLES FROM THE PERSPECTIVES OF TRANSLATORS AND AUDIENCE: A CASE STUDY ON SKIPPED L3 IN THE TV SERIES GRIMM (SEASON 1) = CÁC CHIẾN THUẬT DỊCH NGÔN NGỮ THỨ BA TRONG PHỤ ĐỀ PHIM TRÊN QUAN ĐIỂM CỦA DỊCH GIẢ VÀ KHÁN GIẢ - TRƯỜNG HỢP NGHIÊN CỨU: PHIM TRUYỀN HÌNH GRIMM (SĂN LÙNG QUÁI VẬT) MÙA 1 - Phạm, Hồng Anh (2020)
This paper utilized the TV series Grimm (season 1) to investigate the perception of translators and audience towards third language (L3) translation strategies. By using the term L3, the researcher aimed at any languages other than the main language used in the source text (ST). Specifically, for translators, it aimed at exploring the possible difficulties they encountered when subtitling skipped L3 (i.e. the untranscribed or untranslated L3 in the original English subtitles) in relation to their choices of translation strategies. As for audience, the goal was to find possible inter-relations between their selections and their language competencies. To achieve these objectives, both qualitative and quantitative approaches were utilized, corporealized by document observation, interview and questionnaire.